RETRACTED: Risk assessment of R&D projects: a new approach based on IVIF AHP and fuzzy axiomatic design (Retracted Article) - Ilbahar, Esra; Cebi, Selcuk; Kahraman, Cengiz (IOS PRESS, 2022)
Both national and international encouragements for research and development (R&D) projects have been growing worldwide. Since R&D projects include various uncertainties related to time, technology, finance, and knowledge, risk management studies are highly significant for the success of these projects. In risk management, all of the potential actions that might have negative impacts on the processes or outputs of a project should be determined, and if it is possible, their negative impacts should be reduced before the project starts. In this study, after risks in R&D projects are determined, the alternative projects are prioritized with respect to these risks by using an approach based on interval-valued intuitionistic fuzzy AHP and fuzzy information axiom. Interval-valued Intuitionistic Fuzzy Analytic Hierarchy Process (IVIF AHP) is used to determine the importance degrees of the determined risk factors while fuzzy information axiom is used to evaluate R&D projects considering these risk factors. It is revealed that the most important risk is Abnormal changes in cost while the least important one is Deficiencies in contract articles.
Keywords: R&D; risk assessment; intuitionistic fuzzy sets; AHP; fuzzy information axiom; PRODUCT DEVELOPMENT; MANAGEMENT; SELECTION; ENVIRONMENT; TOPSIS; Computer Science